COVER AND TABLE OF CONTENT - Pembelajaran, Matematika dan (IAIN Ambon, 2024)
1. Students' Trigonometric Representation Translation Process Through GeoGebra-Integrated STAD Cooperative LearningThis article explores the effectiveness of integrating GeoGebra with the STAD (Student Teams-Achievement Divisions) cooperative learning model in enhancing students' understanding of trigonometric representations. The study examines how this combination facilitates the translation of mathematical concepts, fostering better engagement and comprehension among learners. 2. A Didactical Design for Teaching Continuity of FunctionThis study presents a didactical design aimed at teaching the concept of continuity in functions. It outlines instructional strategies, learning activities, and assessment methods that promote deeper understanding of continuity, ensuring that students grasp this fundamental concept effectively through structured learning experiences. 3. Analysis of Students’ Cognitive Structures in Failed Mathematical Proof ConstructionThis article analyzes the cognitive structures of students who encounter difficulties in constructing mathematical proofs. By examining the common misconceptions and thought processes that lead to failures, the study provides insights into how educators can better support students in developing rigorous proof-writing skills. 4. HOTS-Based Student Worksheet Development to Improve Students’ Visual Thinking Skills in Solving Calculus ProblemsThis research focuses on the development of Higher Order Thinking Skills (HOTS)-based student worksheets designed to enhance visual thinking in calculus problem-solving. The article discusses the design process, implementation, and the impact of these worksheets on students' ability to visualize and solve complex calculus problems. 5. Analysis of Imperfection of Mathematical Identity in Problem-SolvingThis article investigates the imperfections often encountered in mathematical identities during problem-solving processes. By analyzing common errors and misconceptions, the study aims to provide strategies for educators to address these issues, ultimately leading to improved problem-solving skills among students. 6. Identification of Students' Techno-Mathematical Literacies (TML) Abilities: Preliminary ResearchThis preliminary research identifies and assesses students' abilities in techno-mathematical literacies (TML). The study examines how well students can integrate technology with mathematical concepts, highlighting areas for improvement and suggesting instructional approaches to enhance TML competencies in the classroom.